Model Hidrologi Produksi Air Bulanan Bagian II : Analisis Korelasi Antara Parameter Model dan Karakteristik DAS - Lukman Hidayat; Putu Sudira; Sahid Susanto (agriTECH, 1996)
An automatic parameter optimization routine was presented. Eleven small watersheds (less than 1000 square km) in Central Java were used for calibration. A method for estimating four parameters water yield model was obtained Equations for predicting the parameters were developed on the correlation analysis between model parameters and measurable watershed characteristics.